2022
DOI: 10.1590/fst.02221
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content, antioxidant and antifungal activity of jackfruit extracts (Artocarpus heterophyllus Lam.).

Abstract: Jackfruit (Artocarpus heterophyllus Lam.) is a fruit of tropical and subtropical zones of the world, is an important source of phytochemicals (phenolic acids, flavonoids and tannins). Several studies have associated phytochemicals with antioxidant and antimicrobial properties. The objective of this work was to analyze the polyphenolic content, the antioxidant and antifungal properties of jackfruit extracts on phytopathogenic fungi. Two phenolic extracts of jackfruit of different maturity level (J1-J2) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…This study also showed the abundance of HJ leaf polyphenols in 80% HEE. Flavonoids exhibit anti-inflammatory, antioxidant, anti-angiogenic and anti-carcinogenic activities (Shi et al, 2018;Chavez-Santiago et al, 2021;Zapata et al, 2021). As presented in Table 1, HWE contained 1.10 mg QUE/g of the lowest TFC value, which is similar to the TPC values of 149.54 mg QUE/g, which is the highest TFC found in 80% of HEE, and consistent with the TPCs.…”
Section: Tpc and Tfcsupporting
confidence: 70%
“…This study also showed the abundance of HJ leaf polyphenols in 80% HEE. Flavonoids exhibit anti-inflammatory, antioxidant, anti-angiogenic and anti-carcinogenic activities (Shi et al, 2018;Chavez-Santiago et al, 2021;Zapata et al, 2021). As presented in Table 1, HWE contained 1.10 mg QUE/g of the lowest TFC value, which is similar to the TPC values of 149.54 mg QUE/g, which is the highest TFC found in 80% of HEE, and consistent with the TPCs.…”
Section: Tpc and Tfcsupporting
confidence: 70%
“…Free radical scavenging activity is an indicator of antioxidant activity. The polyphenols and flavonoids in plants are highly reactive to free radicals, so determining the content of these compounds in selected plant extracts is also indicative of antioxidant activity (Aryal et al, 2019;Chavez-Santiago et al, 2021;Zapata et al, 2021). The TP and TF content of GRE is reflected in Table 1.…”
Section: The Total Phenolic and Flavonoid Content And And Antioxidant Activities Of Grementioning
confidence: 99%
“…[140] The Artocarpus heterophyllus extracts have a high content of polyphenols like flavonoids and these compounds were found to be have strong anti-oxidant capacity. [13] Table (2)…”
Section: Phytochemical Activitymentioning
confidence: 99%